A study on the effectiveness of programs and activities held by the Manila City Library system in the promotion of its library - Generao, Christian Arne B.; Aguirre, Vyva Victoria M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2008)
Public libraries, aside from schools, serve as the cornerstone of the education of the community in which these are situated. Apart from its collection, the extent of a public library's services such as its programs and activities must be taken into consideration not only to promote itself as an institution but also to meet the needs and expectations of its patrons towards quality service. It is for this reason that this study focused on the effectiveness of the programs and activities conducted by the Manila City Library System.
A total of 117 patrons of the whole library system were surveyed aside from the interviews conducted with the 9 branch librarians. A number of annual reports of all the branch libraries were considered in assessing the effectiveness of the programs and activities. The survey questionnaire was based on Borja's questionnaires that she used in her study (Borja, 2007). The interview questions were devised according to the needs of the study.
The interviews showed that the librarians still find means to deliver service the best way possible in spite of the unstable situation of the budget for the library system. However, additional financial support from the government will be of great help.
The data gathered from the survey questionnaires revealed that: (a) majority of the respondents (75.21) are in the college level; (2) half of the respondents (50.00) frequent the library thrice a week; only almost a quarter (20.59) frequent the library everyday; (c) majority of the respondents (67.52) are unaware of the library's programs and activities; out of those who are aware of the library programs and activities (32.48), majority (97.37) have participated; (e) majority of the respondents who have participated (94.59) have enjoyed and found the programs and activities worthwhile; (f) majority of the respondents who have participated (48.65) seldom attended the programs and activities; (g) only a fraction of the respondents who have participated (27.03) regularly attend the programs and activities; and (i) most of the respondents stated that it would be beneficial for the whole library system and the patrons alike if there would be additional tutorial services, not only of academic and electronic nature but also of livelihood. Some also suggested the expansion of the collection to a much timely one and also the expansion of the library's network to reach more people.
Recommendations of the researcher included (a) the provision of additional budget for acquisition of printed and electronic resources and equipment, for further promoting the library through taking in-house storytelling and reading programs to schools and depressed areas in the city, and for further training of library personnel to conduct extensive library orientations, tours and seminars; (b) the establishment of consistently open lines of communication among the patrons, barangay/district officials and the library system for a combined effort for reaching the higher city officials and NGO's and, (c) a further study to determine the specific effects of the programs and activities to public library usage that could possibly discuss an in-depth analysis of the students' and children's needs as a different sector in the society which may also help the school libraries in Manila.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Manila City Library; Libraries -- Public relations -- Philippines -- Manila; Public services (Libraries) -- Evaluation. -- Philippines -- Manila